Sinyal dan Sains : Potret Ketimpangan Digital dalam Akses Pembelajaran di Kalangan Siswa SMAN 2 Sungai Tarab - Rizal Mulya Arif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the digital divide in learning access among 10th-grade students at SMAN 2 Sungai Tarab. Data were collected using a closed questionnaire containing 20 items with positive and negative statements on a 4-point Likert scale. The study was conducted over four days (May 21–24, 2025) and focused on four aspects: ownership of digital devices, internet signal quality, digital literacy, and academic achievement. The findings indicate that all four aspects fall within the moderate category of digital divide, with average scores as follows: digital device ownership (2.66), signal quality (2.57), digital literacy (2.76), and academic achievement (2.50). Digital literacy showed the highest level of disparity, highlighting that some students still struggle to use digital devices effectively. Academic achievement showed the lowest disparity but is still influenced by the other factors. This study reinforces previous research that the digital divide remains a barrier to equitable education, especially in non-urban areas. Collaborative efforts are needed to improve infrastructure and enhance students’ digital skills to ensure more inclusive and equitable access to digital learning.